Halal Ecosystem Micro Small and Medium Enterprises Through The Integration of Value Chain and Green Strategies - Rofik Efendi; Natalina, Sri Anugrah Natalina; Fani Ma’sumatul Maghfiroh; Wiwik Kusumaning Asmoro (Istithmar, 2024)
The halal lifestyle has become relevant for many people, not only for Muslims, but also for those who are not Muslims. The creation of the halal industrial area is a manifestation of the government’s seriousness in creating a halal-based and environmentally friendly business climate. The government facilitates the halal guarantee financing component, for example, there are subsidies and financial support for MSMEs in the halal product certification process. Infrastructure is prepared in the form of logistics and halal supply chains which are different in each sector. Infrastructure as a preparation for raw material logistics and the chain sector to support industrial strengthening, among others; food, pharmaceuticals, tourism, cosmetics and finance. Optimizing green halal products with the concept of halal supply chain in developing a halal ecosystem for MSMEs in Indonesia is by strengthening the four pillars of the halal industry. MSME actors already know the existence of the environmental cost account component as a form of implementing green accounting, but the problem is the truth or suitability and accuracy of the sacrifices made by the business unit with the characteristics of the definition of environmental costs.